Sentiment Analysis of the Impact of the Covid-19 Pandemic on Students and College Students through Twitter Social Media - Yuyun Khairunisa (2022)
The Covid-19 pandemic has had an impact on adjusting the implementation of economic and social activities as well as education by prioritizing public safety and health, including students. The purpose of this research was to obtain the results of sentiment analysis on the impact of the pandemic on students by extracting opinions in the form of text on Twitter social media. The benefit of the results of the sentiment analysis is that solutions can be found for those affected by the pandemic. The method used in sentiment analysis consists of 5 stages, namely data collection, text preparation, sentiment detection, sentiment classification, and output analysis. The research results stated that negative sentiment was the largest sentiment, namely 88%, followed by positive sentiment as much as 6% and neutral sentiment as much as 5.3%.